Sweat Gland Denervation in Cerebellar Ataxia with Neuropathy and Vestibular Areflexia Syndrome (CANVAS). Issue 1 (5th April 2016) - Umeh, Chizoba C.; Polydefkis, Michael; Chaudhry, Vinay; Zee, David S.
Abstract: Cerebellar ataxia with neuropathy and vestibular areflexia syndrome (CANVAS) is a newly recognized disorder characterized by cerebellar ataxia, nonlength‐dependent sensory impairment, and bilateral vestibular loss. Sudomotor dysfunction has been described in CANVAS; however, the underlying pathology is not well characterized. To describe novel histopathological features of this syndrome, 2 siblings are presented who had CANVAS with unique findings of sweat gland denervation. Skin biopsy testing was performed to assess sudomotor structure and revealed markedly reduced sweat gland nerve fiber density below the 2.5th percentile in both patients. These histopathological findings suggest that postganglionic sudomotor dysfunction is an additional feature of CANVAS.